ELABORAÇÃO E AVALIAÇÃO DA COMPOSIÇÃO CENTESIMAL DE BISCOITO TIPO SALGADO - Schöffer, Jéssie d. N.; Rosso, Ana C.; Knorst, Gabriel; Vicenzi, Raul; Kinalski, Tenisa; Poll, Raysa; Führ, Zuleica W. (Salão do Conhecimento, 2013)
Resumo